Rheological behavior of fibre-filled polymer melts at low shear rate. Pt. 2, Experimental investigation - Hausnerova, B.; Honkova, N.; Lengalova, A.; Kitano, T.; Saha, P. (Polimery, 2022)
In this study, rheological properties of carbon fibre-filled polypropylene and polyethylene melts at low shear rate were measured using a cone-plate rheometer. The melts with high fibre loading show complex shear flow depending on the fibre concentration, its length and length distribution, as well as on shear rate and matrix characteristics. The existence of yield stress and time-dependent or shear-strain-dependent properties are also discussed and compared with previous results. The shear flow in the narrow gap of cone-plate rheometer influences the fibre assembly. However, the effect of low shear rate on the structure of fibre assembly is negligible.